IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI BERBANTUAN E-LKPD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Aida Fitriana; I Dewa Putu Juwana (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
Learning outcomes are the abilities possessed by students after carrying out the learning process in achieving a learning goal. The purpose of this research was to improve the mathematics learning outcomes of class VIII.3 students of SMPN 6 Denpasar through the application of E-LKPD assisted differentiation learning. This research is classroom action research which consists of two cycles. The stages of each cycle include planning, action, observation, and reflection. The research instrument used was a multiple choice test. In the pre-cycle the average score of students' mathematics learning outcomes was very low and there were only 10 students whose scores exceeded the KKM. In cycle I, the average value of students' mathematics learning outcomes increased to 78.60 and classical learning mastery was 40%, but did not meet the indicators of success. In cycle II, the average scores for learning mathematics and mastery of classical learning have achieved indicators of success, namely 86.40 and 74%. Based on these results it can be concluded that the application of E-LKPD assisted differentiated learning can improve student mathematics learning outcomes.